Active compounds of lemon grass (Cymbopogon citratus): a review (Research, Society and Development, 2021)
The present study aimed to present a broad and current survey in relation to the active compounds of lemongrass (Cymbopogon citratus) and the functionalities exerted by it, both in vitro and in vivo. To this end, a literature review was carried out, which brought together the scientific knowledge on aspects of the functional properties of lemongrass. The survey had as a time frame the last 10 years (2011 to 2021). Articles in Portuguese and English were used. The bibliographic survey presents aspects of medicinal plants, their use and their active compounds. It presents the characteristics of Cymbopogon citratus, its active compounds and its functionalities. Through the searches it was found that this plant has compounds that are in charge of calming, antifungal, antimicrobial, among others. It was concluded that these therapeutic actions are produced mainly by the presence of citral, a component in greater quantity in the essential oil of this herb, and for having proven effectiveness of its benefits and being easy to grow, this herb is an herbal medicine. easily accessible to the general population, both for the control of human diseases and for the control of pests in animals.